A kora újkori magyar és lengyel–litván rendi országgyűlés összetétele - Képes, György (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2026)
The emergence of both the Polish and Hungarian bicameral assemblies were the result of a de-facto merger of the larger (or full) royal council and the assemblies of the nobility that had gradually become representative. In Poland, the simultaneous but physically separate sitting of the two houses, the Senate and the House of Envoys, can be observed from the mid-15th century and has been considered permanent since the Diet of Piotrków of 1493. In Hungary, the same changes (the formation of the upper and lower chambers) occurred a hundred years later and were finally enshrined in Act I (after the coronation) of 1608. However, it can also be observed that, despite their many similarities, the parliaments of the two Eastern Central European countries followed different paths of development. The most striking difference – apart from the federal character of the post-1569 Polish-Lithuanian joint Seym - was that while the Polish-Lithuanian Diets were attended exclusively or almost exclusively by the nobility, the Hungarian Diets were open to other social classes as well, albeit with a much smaller representation than that of the nobility.